Sensitive flow-injection spectrophotometric analysis of bromopride - Lima, Liliane Spazzapam [UNESP]; Weinert, Patricia Los [UNESP]; Pezza, Leonardo [UNESP]; Pezza, Helena Redigolo [UNESP] (Elsevier B.V., 2014)
A flow injection spectrophotometric procedure employing merging zones is proposed for direct bromopride determination in pharmaceutical formulations and biological fluids. The proposed method is based on the reaction between bromopride and p-dimethylaminocinnamaldehyde (p-DAC) in acid medium, in the presence of sodium dodecyl sulfate (SDS), resulting in formation of a violet product (lambda(max) = 565 nm). Experimental design methodologies were used to optimize the experimental conditions. The Beer-Lambert law was obeyed in a bromopride concentration range of 3.63 x 10(-7) to 2.90 x 10(-5) mol L-1, with a correlation coefficient (r) of 0.9999. The limits of detection and quantification were 1.07 x 10(-7) and 3.57 x 10(-7) mol L-1, respectively. The proposed method was successfully applied to the determination of bromopride in pharmaceuticals and human urine, and recoveries of the drug from these media were in the ranges 99.6-101.2% and 98.6-102.1%, respectively. This new flow injection procedure does not require any sample pretreatment steps. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Bromopride; Flow injection analysis; Pharmaceuticals; Urine